Supporting Impact with Evidence: A Content Analysis of Project Completion Reports. Issue 8 (3rd August 2018) - Carneiro, Bia; Garbero, Alessandra
Abstract: Project Completion Reports (PCRs) are used by development institutions to tell a project's story – achievements, failures, and learning. As such, they should provide evidence of effectiveness in bringing about development. But is this the case? Descriptive content analysis was applied to assess the extent of evidentiary support presented in the International Fund for Agricultural Development's end of project documentation, employing a custom conceptual framework to classify claims about project results found in PCRs based on results level, tone, evidence sources, and themes. Findings show the majority of claims relate to output or outcome level results and are positive, though not explicitly supported by evidence. The lack of evidence-based reporting carries implications to the objective measurement of development effectiveness.